Failure Analysis of Metal Oxide Surge Arrester on Busbar of 220kV Substation. Issue 2 (February 2021) - Zhang, Dewen; Huang, Hai; Zhao, Xiangyu; Shang, Fang; Zhu, Linlin; Hu, Xiaoxu
Abstract: MOA (Metal Oxide Arrester) is widely used in power systems because of its good nonlinear volt-ampere characteristics and current-carrying capacity. Its long-term operation may have defects such as heat generation and reduced insulation performance. This paper analyzes a 220kV substation bus lightning arrester, collects fault recording information, points out the cause of the fault and puts forward corresponding preventive measures.